DETERMINAN PENENTU PERTUMBUHAN DANA PIHAK KETIGA PERBANKAN SYARIAH DI INDONESIA - Setiawan Setiawan (Masoem University, 2018)
Islamic banking has continued weakening of growth in Depositor Funds gathers. The lowest growth occurred in the year 2015 which growth reached 6.11%. The purpose of this research was to find out what internal factors that can affect the growth of Depositor Funds of Islamic banking in Indonesia. Internal factors that supposedly influential include: Operating Espenses to Operating Revenue (BOPO), Training Costs, Promotion Cost, Financing to Deposit Ratio (FDR), the number of office network, and Non-Performing Financing (NPF). This research hypothesis testing using the analysis with the model of Structural Equation Models (SEM). The analysis used Partial Least Square (PLS), so it can be known how much of the independent variables are observed with influential factors hypothesized. The research found that the latent variable Internal factors influence on Depositor Funds. The variable encompasses Internal factors explaining the Depositor Funds amounting to 15.6%, the rest is explained by other variables that are not included in this research model.